Prevalence and Associated Factors of Stunting Among Children Aged 6–59 Months in Delanta District; North East Ethiopia - Tadesse SE; Mekonnen TC (Nutrition and Dietary Supplements, 2020)
Sisay Eshete Tadesse, Tefera Chane Mekonnen Department of Public Health, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Sisay Eshete Tadesse Email sisliyu21@gmail.comBackground: Under-nutrition among under-five children is a global public health problem. Sub-Saharan Africa and South Asia were the home for three-fourth of the world’s stunted children. There is a disparity in the prevalence and associated factors of under-nutrition across regions and cities.Objective: To assess the prevalence and associated factors of stunting among children 6– 59 months in Delanta district.Methods: A community-based cross-sectional study design was conducted among 342 systematically selected children aged 6– 59 months from April to May 2017 G.C. The sample size was calculated by single population proportion formula. Data were collected by a structured questionnaire, SECA weight measurement, and height measuring board. After collection, data were entered into Epi data version 3.1 for cleaning and transferred to SPSS version 24.0 for analysis. Anthropometric data were analyzed using WHO Anthro 2005 software. Descriptive statistics were done and the result was reported by frequency, percentile, and mean ± standard deviation. Variables having a p-value <  0.25 in bivariable binary logistic regression were transported to multivariable binary logistic regression to identify factors associated with stunting. In multivariable model, the statistical significance was declared by using adjusted odds ratio with 95% confidence interval and a p-value <  0.05.Results: The mean age of the study participants was 25.12± 15.45 months. The prevalence of stunting was 22.1% (95% CI: 17.6, 26.5). Late initiation of breastfeeding (AOR=2.4; 95% CI: 1.2, 4.9), postnatal care (AOR=0.3, 95% CI: 0.1, 0.9), and repeated episodes of respiratory infection (AOR=4.9; 95% CI: 1.8, 12.8) were factors associated with stunting.Conclusion and Recommendation: Stunting is a moderate public health problem. Late initiations of breastfeeding, not attending postnatal care and repeated respiratory infection were factors associated with stunting. So, strengthening implementation of baby-friendly hospital initiatives, strengthening of postnatal care service utilization and prevention and control of respiratory infection should be included in the prevention strategies of stunting.Keywords: prevalence, stunting, associated factors, cross-sectional, Ethiopia and Delanta